Development of Local Instructional Theory Topic Division Based on Realistic Mathematics Education in Basic School - Rendy Novri Yolanda; Ahmad Fauzan (Postgraduate School, Universitas Negeri Padang, 2019)
This research is motivated by barriers to student learning on the topic of division. The problem solving ability is the impact of the less effective learning that has been carried out. In this case, the importance of learning is based on Realistic Mathematics Education (RME). The research was conducted by developing valid, practical and effective Local Instructional Theory (LIT) through development research revealed by Gravemeijer & Cobb. The subjects of the trial came from third grade students of SDN region IV, Koto Tangah sub-district, Padang City. Research is supported by data collection techniques in the form of document analysis, observation, interviews, questionnaires, and tests. Data analysis was performed using descriptive statistics and parametric statistics. Validation results show valid LIT which can be seen from aspects of content, language, didactic, and presentation that are in accordance with the principles and characteristics of the RME. The trial results also show very practical categories that are seen in terms of ease of use, student readability and availability of time so that students can carry out a series of LIT learning activities. In addition, LIT has an impact on students' effective problem solving abilities. This can be seen from the comparison of the average mathematical problem solving abilities of students who use LIT by not using LIT. The hypothesis test addresses the experimental class data higher than the control class data. Keywords: LIT, RME, Division